(3RjGOI GdLGeY GdUZjQ ef MOjK GdHTjQ GdfPjQs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3YHO GdbGOQ GdbQGbi GdTGaYi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hUdi Gddg Ydi SjOfG eMeO gPG Pjd Ydi cJGHi GdeSei HGdLGeY GdUZjQ ef MOjK GdHTjQ GdfPjQ SejJg RjGOI GdLGeY QehRg cQehRg hGdJQJjH cGdJQJjH s
(3BNQgG (B:s
(3Yf CHj gQjQI (B( (3bGd (B) (3GdjghO eZVhH Ydjge hGdfUGQi VdGd BNQ GdcJGH Je GdcJGH GdeHGQc RjGOI GdLGeY GdUZjQ ef MOjK GdHTjQ GdfPjQ s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
Keywords: (3GdMOjK h GdeUWdMs